THE ROLE OF THE OBOE IN THE KAZAKH FOLK ORCHESTRA - Gaukhar Mukasheva (Theoretical Hypotheses and Empirical Results, 2025)
Contemporary musicology pays considerable attention to the study of timbral characteristics and the artistic functions of wind instruments. Among them, the oboe occupies a special place – an instrument with a unique expressive nature and a rich history, which has been an important part of the world’s musical culture for centuries. Today, research on the oboe encompasses a wide range of areas, from the analysis of solo and chamber repertoire to the study of its functions within the symphony orchestra. However, in the context of Kazakh musical culture, this instrument has been studied insufficiently. This article examines the characteristics of the oboe’s sound in the Kazakh folk orchestra, as well as its role in the interpretation of kuys. The formation of the Kazakh folk orchestra in 1934 under the leadership of Akhmet Zhubanov marked an important stage in the development of Kazakhstan’s musical culture. The new ensemble not only unified national instruments into a single artistic system but also incorporated certain elements of European orchestral practice. This allowed for an expansion of its timbral possibilities and gave the folk orchestra’s sound a richness of color characteristic of symphonic orchestration. A special place in this renewed orchestral palette was occupied by the oboe, which possesses a unique timbral quality and expressive power.